PARADIGMATIC RELATIONS OF COMPARATIVE PHRASEOLOGICAL UNITS IN ENGLISH AND KARAKALPAK LANGUAGES - Saparov, Salamat Perdebaevich; Bayjanov, Saparniyaz Yagmirbaevich (SCIENCE and SOCIETY, 2026)
This article presents a comparative analysis of the paradigmatic relationships of comparative adjectival phraseological units in English and Karakalpak. The study examines their semantic polysemy, the formation of synonymic series, structural–semantic characteristics, and intensifying functions. The findings reveal significant typological similarities between the phraseological systems of both languages and highlight the national-cultural specificity and imagery of comparative expressions.
Keywords: comparative phraseological units; adjectival idioms; polysemy; synonymy; paradigmatic relations; English; Karakalpak